EtIDip (EtIPr)—Synthesis, Characterisation and Reactivity of a Robust, Backbone-Modified N-Heterocyclic Carbene and Group 13 Element Complexes - Huanhuan Dong; Albert Martinez-Segura; Riley W. Kelehan; Connor Bourne; Aidan P. McKay; Alexandra M. Z. Slawin; David B. Cordes; Andreas Stasch (Inorganics)
We report the synthesis, characterisation and reactivity of the stable imidazol-2-ylidene EtIDip (EtIPr), {EtCN(Dip)}2C:, Dip = 2,6-iPr2C6H3, as a chemically robust alternative to IDip (IPr), {HCN(Dip)}2C:. The N-heterocyclic carbene EtIDip could be further converted to the oxidised species [EtIDipCl]Cl, EtIDipF2, EtIDipO, and EtIDipSe, and the group 13 element complexes EtIDipEX3, with E = B, X = Br; E = Al, X = I; E = Ga, X = I; E = Al, X = H. The properties of the EtIDip and IDip ligands are compared and the molecular structures of (DipNCEt)2, [EtIDipH]Cl, [EtIDipH]I, EtIDip, [EtIDipCl]Cl, EtIDipF2, EtIDipO, EtIDipBBr3, EtIDipAlI3, EtIDipGaI3, and EtIDipAlH3 have been determined.